Shape-based filter for micro-aneurysm detection. (June 2020) - Zhang, Xinpeng; Xiao, Zhitao; Zhang, Fang; Ogunbona, Philip O.; Xi, Jiangtao; Tong, Jun
Abstract: Automatic detection of micro-aneurysm in color retinal image is important for early screening and diagnosis of diabetic retinopathy. In this paper, a new method is proposed for micro-aneurysm detection based on circular bilateral Gabor filtering. Firstly, a circular bilateral Gabor filter is developed to extract micro-aneurysm candidates. Secondly, false positives are reduced by eliminating small vessels through a process involving local gradient analysis. The proposed method is tested on the retinal images from the Retinopathy Online Challenge database and Tianjin Medical University Metabolic Diseases Hospital. Evaluation results at both image and lesion level demonstrate the efficacy of the proposed method in detecting micro-aneurysm accurately.